Needs assessment survey among healthcare professionals to implement the 4Ms framework: a cross-sectional study from Qatar - Hanadi Al Hamad (12229412) (2024)
Background Worldwide, the evidence-based 4Ms framework of the Age-Friendly Health System (AFHS) improves the experience of caring for older adults. This study aimed to examine healthcare professionals’ perceptions, attitudes, and behaviors regarding the AFHS and 4Ms before they were implemented. Methods This study was a questionnaire-based survey of 252 healthcare professionals in geriatrics and long-term care departments, Rumailah Hospital, Acute Care Services in Hamad General Hospital, and home healthcare services to assess their perceptions, attitudes, and behaviors regarding 4Ms from November 1, 2022, to July 31, 2023. Results Most respondents acknowledged the benefits of providing care through AFHS. However, only 62% of respondents reported using the 4Ms framework. The most commonly used types of age-friendly care provided by health care professionals were reviews of high-risk medication use (64.2%) and screening for mobility limitations (55.8%). Conclusion The findings suggest that there is a need for more training and education regarding the 4Ms framework for health care providers. This training should focus on specific aspects of the framework, such as how to assess what matters most to older adults; how to manage their mobility, mentation, and medication; and how to coordinate care across settings. Other Information Published in: The Aging Male License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13685538.2024.2401161